Molecular Detection of Biofilm-Related Genes (mrpA, fimH) in Urinary Tract Co-Infections - Abdulshafi, Mohammed Abdulwahab; Alkhafaji, Marwa Hameed (Iraqi Journal of Science, 2026)
Urinary tract co-infections are particularly significant due to their potential to facilitate the transfer of biofilm formation genes between pathogens. The research aims to uncover hidden partners for catheter patients and determine, that isolates producer biofilm. 131 samples were collected from urinary catheter patients, during the period from October 2023 to March 2024. Each sample was cultured on mannitol salt agar and MacConkey agar plates to differentiate between G+ve and -ve bacteria. Then, identification was completed by using chemical tests and the Vitek 2 compact system. Bacterial DNA was extracted, and specific primers were designed to amplify mrpA and fimH genes using multiplex PCR. 96/131 (73.28%) of samples showed positive growth, while 35/131 (26.71%) showed negative growth. On MacConkey agar, the results showed a growth percent of 93.75% (90 samples), while on mannitol salt agar, the growth percent was as low as 6.25% (6) samples. The results of MacConkey agar showed single species 68/90 (75.55%), double 7/90 (7.77%), and triple 15/90 (16.66%). Triplicates were Proteus mirabilis, Klebsiella pneumoniae and Escherichia coli, which were the most prevalent (66.66%). Biofilm detection was done using three methods, congo red agar method, microtiter plate method, and electron microscopic examination. In conclusion, P. mirabilis was found to reduce the biofilm formation potential of K. pneumoniae and E. coli. The mrpA gene was detected in 60% of K. pneumoniae, P. mirabilis, and E. coli isolates, while the fimH gene was present in 70% of K. pneumoniae and E. coli isolates. Notably, E. coli isolates had a higher percentage of the mrpA gene than fimH, likely due to horizontal gene transfer.